Cat or marten?: Ailouros in Baruch 6:21 [22] and in Aesop's fables - Wojciechowski, Michał (Biblische Notizen, 2014)
Ailouroi in Baruch 6:21 and Aesop (7, 16 Perry / Hausrath) are not cats, but martens.